A synthetic NKG2A engager enables long-term persistence of HLA-deficient allogeneic engineered Tregs - Tingxi Guo; Kaya R Epstein; Maegan E Hoover; Nathan W Zammit; Jennifer Y Yam; Scott Hussell; Sophia Hernandez; Abigail Doherty; Payam Zarin; Martina Sassone-Corsi; Lindsay Webb; Gene I Uenishi; et al. (EMBO Molecular Medicine, 2026)
Abstract Allogeneic cell therapies offer a scalable and off-the-shelf alternative to the autologous approach, but immune rejection, particularly by natural killer (NK) cells following human leukocyte antigen (HLA) ablation, remains a major barrier to their persistence. Here, we report an improved synthetic NKG2A engager to selectively inhibit NKG2A⁺ NK cells while avoiding activation of NKG2C⁺ subsets, thereby overcoming a key limitation of the natural ligand HLA-E. Engineered regulatory T cells (EngTregs) lacking HLA and expressing the engager were protected from in vitro NK cell-mediated cytotoxicity more effectively than previously reported NK inhibitory strategies. In humanized mouse models, EngTregs persisted for up to 12 weeks, whereas unprotected cells were rapidly rejected. Incorporation of the engager into a clinically compatible dual-AAV EngTregs preserved Treg identity and function while conferring resistance to immune rejection. Together, these findings establish the improved NKG2A engager as an effective synthetic immune-evasion strategy and provide a clinically translatable approach to enable durable persistence of off-the-shelf EngTreg therapies.